Keeping our heads above the waters the contingency plan for storm surge of Barangay Tanao, Batad, Iloilo - Garcinela, Arjun (Iloilo City University of the Philippines Visayas, 2015)
Last Novemeber 8, 2013, the Municipality of Batad was among the hardest hit areas in the Philippines by Typhoon Yolanda. Within the municipality, Barangay Tanao was one of the barangays which aside from the. very strong winds, also experienced a storm surge that almost wiped out all the houses located along and even up to 300 meters landward from the shoreline. With the recorded damage of the Typhoon and the storm surge in the barangay and guided by several legal mandates on contingency planning, the students of diploma in Urbaan and Regional Planning of the University of the Philippines in the Visayas conducted a study that would facilitate and assist Barangay Tanao in the formulation of its own contingency plan for storm surge. Primarily, the objective of the study was to determine the extent of preparedness of Barangay Tanaoto respond and manage the underlying impacts of a storm surge and to formulate the storm surge plan of the barangay in the hope to build the barangay's resiliency to dsasters. Primary and secondarycollection methods such as the conduct of participatory Capacity and Vulnerability Assessment (PCVA), Focus Group Discussions, and Workshops using the Contingency Planning Forms provided in the Contingency Planning for Emergencies' manual for Local Government Units were used in the study. The results were then analyzed using thematic mapping with the aid of Manifold, a Geographical Information System (GIS) that generated the Storm Surge Risk Map of the barangay. A validation workshop was also conducted and the results were further presented to a group of panellists composed of representatives from the barangay, the executive and the legislative departments of the municipal government of Batad, NGO and the Department of Interior and Local Government (DILG) and the Office of the Civil Defence (OCD). Results from a variety of methods showed that the barangay is at riskto storm surge due to a number of factors affecting its exposure, vulnerability and capacity. a number of natural and physical resources of the barangay such as the mangrove area, a fishpond, some rice fields and the barangay road connecting the barangay to the rest of the municipality are also within the storm surge area. There is clear need to step up the baragay's initiatives to lower or reduce its risk by enhancing and mproving ts capacities,reducing its exposure to the potential hazaed and responding appropriately to its current vulnerabilities. The barangay maybe faced with challenges ut there is strong will from among the community leaders and its residents to work together to improve the resiliency of the whole community. These conditions -- along with relevant researches on DRRM and international and national legislations in place -- shaped the formulation of a Contingency plan for Storm Surge f the barangay/. This document includes some recommendations related to improvements on policy formulation, planning and budgeting and project implementation and on networking to help the barangay reduce its risk to storm surge and eventually enhance its disaster resiliency.
Research Paper (P210.1 - Planning Workshop)